1998
DOI: 10.1677/joe.0.1570237
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of retinoic acid on uncoupling protein-1 and leptin gene expression

Abstract: All-trans-retinoic acid (RA), one of the active metabolites of vitamin A, can increase the expression of uncoupling protein-1 (UCP1) gene. To determine whether RA stimulates brown adipose tissue (BAT) thermogenesis and modulates leptin gene expression in vivo, 6-month-old, vitamin-A sufficient, F344 BN rats were administered a single dose of RA (7·5 mg/kg, i.p.) or the 3 -adrenergic receptor ( 3 AR) specific agonist, CGP 12177 (0·75 mg/ kg). Levels of UCP1 mRNA in BAT and leptin mRNA in perirenal white adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 31 publications
7
50
1
1
Order By: Relevance
“…43 In the last years, it has become increasingly clear that RA is a modulator of fat metabolism that promotes fat mobilization (and=or apoptosis) in vivo and the transformation of mature adipocytes into cells less capable to store triglycerides and more capable of using fatty acids. Mice acutely treated with RA lose body weight and adiposity 22,28,29 and, overall, the effects of acute RA-treatment on the expression of UCPs -the previously reported induction of BAT UCP1 and UCP2 levels 22,27,28 and the induction of muscle UCP3 reported here -fit well in a framework of enhanced fat metabolism triggered by RA. In this framework, RA induction of UCPs may serve to facilitate the handling of lipids as a fuel, either for heat production or ATP production.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…43 In the last years, it has become increasingly clear that RA is a modulator of fat metabolism that promotes fat mobilization (and=or apoptosis) in vivo and the transformation of mature adipocytes into cells less capable to store triglycerides and more capable of using fatty acids. Mice acutely treated with RA lose body weight and adiposity 22,28,29 and, overall, the effects of acute RA-treatment on the expression of UCPs -the previously reported induction of BAT UCP1 and UCP2 levels 22,27,28 and the induction of muscle UCP3 reported here -fit well in a framework of enhanced fat metabolism triggered by RA. In this framework, RA induction of UCPs may serve to facilitate the handling of lipids as a fuel, either for heat production or ATP production.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, studies in humans under high fat diets showed increases of fat oxidation and UCP3 expression in muscle that were not accompanied by increases of circulating NEFA levels. 47,51 Lower levels of adipose leptin mRNA in B6 mice fed vitamin A-supplemented diets is in agreement with downregulation of adipose leptin mRNA levels following acute RA-treatment in rats and mice 27,28 and reduction of circulating leptin levels following dietary vitamin A supplementation in rats. 30 Our results further suggest that retinoids may by themselves exert an inhibitory effect on leptin expression that is not secondary to a reduction of fat content, because the depressed adipose leptin mRNA levels found did not correlate with comparable reductions of the adipose depots mass.…”
Section: Ucp3 and Vitamin Asupporting
confidence: 64%
See 1 more Smart Citation
“…We found inhibition of leptin mRNA expression in the IBAT of tRA-treated mice, whether fed standard chow or vitamin A-deficient diet; the same effect was reported in the perirenal white fat of vitamin A-sufficient rats acutely treated with RA (Kumar & Scarpace 1998) or chronically fed a retinol-supplemented diet (Kumar et al 1999). Considering the marked reduction of IBAT adiposity brought about by tRA treatment (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Adipose tissue have long been recognized as a potential site for the action of RAs, and the two retinoid receptors, RAR and RXR, are both expressed in adipose tissue (Villarroya et al 1999). All-trans-RA has been recently described as new regulator of UCP1 gene and ob gene in rat perirenal white adipose tissue (Kumar & Scarpace 1998), but there are presently no data available regarding its action on the in vitro leptin secretion by human adipose tissue.…”
Section: Introductionmentioning
confidence: 99%